2013
DOI: 10.1007/s00330-013-2950-7
|View full text |Cite
|
Sign up to set email alerts
|

Proton-density fat fraction and simultaneous R2* estimation as an MRI tool for assessment of osteoporosis

Abstract: Objective To investigate multi-echo chemical shift-encoded MRI-based mapping of proton density fat fraction (PDFF) and fat-corrected R2* in bone marrow as biomarkers for osteoporosis assessment. Methods Fifty-one patients (28 female; mean age 69.7 ± 9.0 years) underwent dual energy X-ray absorptiometry (DXA). On the basis of the t score, 173 valid vertebrae bodies were divided into three groups (healthy, osteopenic and osteoporotic). Three echo chemical shift-encoded MRI sequences were acquired at 3 T. PDFF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
107
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 32 publications
(55 reference statements)
9
107
1
Order By: Relevance
“…Our phantom experiments also indicated a positive association between R2* and BMD . A number of authors have previously explored the use of R2* or R2' as markers of osteoporosis, and these parameters have been found to parallel apparent density measured by dual‐energy X‐ray absorptiometry (DEXA) or quantitative CT (QCT) . However, our results indicate that R2* measurements also are influenced by PDFF and cannot be regarded as a pure marker of BMD when fat content varies as well.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Our phantom experiments also indicated a positive association between R2* and BMD . A number of authors have previously explored the use of R2* or R2' as markers of osteoporosis, and these parameters have been found to parallel apparent density measured by dual‐energy X‐ray absorptiometry (DEXA) or quantitative CT (QCT) . However, our results indicate that R2* measurements also are influenced by PDFF and cannot be regarded as a pure marker of BMD when fat content varies as well.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies also support this suggestion. For example, Kühn et al showed that R2* measurements could discriminate normal and osteoporotic patients with reasonably high levels of sensitivity and specificity despite concomitant variations in fat content in osteoporotic individuals .…”
Section: Discussionmentioning
confidence: 99%
“…In the context of osteoporosis, water-fat imaging-based vertebral bone marrow fat fraction was inversely correlated with BMD. [14][15][16] Furthermore, water-fat imaging based bone marrow fat fraction increased after chemotherapy and radiation therapy, thus detecting chemotherapy and radiation-induced bone marrow damage.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Vertebral bone marrow PDFF has been reported to be inversely correlated with BMD. [14][15][16] Furthermore, water-fat imaging has been successfully applied to detect chemotherapy and radiation-induced bone marrow damage.…”
mentioning
confidence: 99%
“…PDFF-based liver fat quantification enables the noninvasive assessment of hepatic steatosis, the hallmark histologic feature of nonalcoholic fatty liver disease, which is estimated to affect 20–30% of the Western population [49]. Further, these techniques allow the simultaneous estimation of fat- and noise-corrected liver iron content using R2* (1 / T2*) quantification from the same acquired CSE MRI data [1012]. R2*-based liver iron quantification enables the noninvasive assessment of diseases that result in liver iron overload, including hereditary hemochromatosis, and blood transfusion–dependent conditions such as thalassemia, sickle cell disease, and bone marrow failure [1318].…”
mentioning
confidence: 99%